1996
DOI: 10.1046/j.1471-4159.1996.67041744.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Myelinogenesis by Dietary Lipids in Rat Brain

Abstract: Our previous work showed an early development of behavioral reflexes in rats whose mothers had been fed, during pregnancy and lactation, a lipid fraction extracted from yeast grown on n‐alkanes (which contain 50% odd‐chain fatty acids) in comparison with controls fed a margarine diet. To clarify whether the observed changes might be linked to an early myelination, we have investigated mRNAs involved in myelin synthesis in the brains of offspring at 5 days of age by northern blot and in situ hybridization. Nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…From studies in rat, it became clear that the brain is clearly sensitive to alteration of dietary lipid intake (Foot et al, 1982). Moreover, myelin formation in the rat brain can be accelerated by dietary lipids (Salvati et al, 1996). Postnatal deficiency of essential fatty acids reduces the mRNA levels of specific oligodendrocyte myelin proteins in the mouse brain (DeWille & Farmer, 1992).…”
Section: Cns Bioavailability Of Dietary Antioxidants and Pufasmentioning
confidence: 99%
“…From studies in rat, it became clear that the brain is clearly sensitive to alteration of dietary lipid intake (Foot et al, 1982). Moreover, myelin formation in the rat brain can be accelerated by dietary lipids (Salvati et al, 1996). Postnatal deficiency of essential fatty acids reduces the mRNA levels of specific oligodendrocyte myelin proteins in the mouse brain (DeWille & Farmer, 1992).…”
Section: Cns Bioavailability Of Dietary Antioxidants and Pufasmentioning
confidence: 99%
“…The amount of probe hybridised to the blot was quantitated on a 2202 Ultrascan laser densitometry. The arrowhead indicates 2.4-kb mRNA PLP [38].…”
Section: Dietary Fatty Acids and Myelinmentioning
confidence: 99%
“…By contrast, in tests, the MOG transcript was detected both in the medulla and cerebellum, suggesting an accelerated gradient of developmental expression in these animals ( fig. 3) [38]. Although it is still not known if an increase in myelin protein mRNAs is due to either an up-regulation of gene expression or mRNA stabilisation mechanism, surely this increase is reflected in an increased number of differentiated oligodendrocytes [38].…”
Section: Dietary Fatty Acids and Myelinmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies in rats have clearly shown the brain to be sensitive to alterations in dietary lipid intake, even with a nutritionally complete diet [25] . Myelin formation in the rat brain can be accelerated by dietary lipids [26] , and postnatal defi ciency in essential fatty acids reduces oligodendrocyte myelin basic protein (MBP) and proteolipid protein (PLP) mRNA levels in the mouse brain [27] . Furthermore, oral feeding of ␥ -linolenic acid (GLA; 18: 2n-6) ameliorates the course of both acute and chronic experimental autoimmune encephalomyelitis [28] .…”
Section: Introductionmentioning
confidence: 99%